Ethic Educations Of Leadership In Tenganan Pegringsingan Traditional Village - Ersa Rahayu Dewi, Putu; Suwindia, I Gede; Sudarsana, I Ketut (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
Every village has a leader. The uniqueness of the leadership of Tenganan Pegringsingan village is interesting to be observed. Therefore, the researcher is interested to observe it with three main problems as follows: 1.How is the leadership system in Tenganan Pegringsingan traditional village? 2. How is the job and leadership function in Tenganan Pegringsingan traditional village? 3. How is the ethics education in leadership system in Tenganan Pegringsingan? with the general objects and specific objects and also the benefits of theoretical and practical. Furthermore, theoretical mapping in this study uses as follows: 1. system theory to distinguish the problem of leader system; 2. structural functional theory to distinguish the problem about the leadership’s job and the function; 3. the value theory to distinguish the problem of leadership ethics education. Whereas, the method used is the method of collecting data as the beginning for accuracy and foresight in preparing the thesis. The method of collecting the data as follows: observation method, interview method, library method, and method of documentation study. After the data collected and processed by using descriptive analysis method is how data processing is done by the way of arranging systematically to get the general conclusion. Based on the research methods, the result of the study can be describe as follows: 1. leadership system of Tenganan Pegringsingan traditional village such as: a. general leadership; b. the role of traditional village; c. devotion of leadership rules; d. the level of krama desa’s structure; e. the relationship between traditional village and the government; f. routine krama desa activities. 2. Tenganan Pegringsingan’s duties and functions of village leadership such as: a. tradition and religion functions; b. political and the law function; c. social and civic security function. 3. Leadership ethics education such as:  a. ehical education in taking decision; b. ethical education in rituals and religions; c. ethical education in environmental management; d. ethical education in maintaining tradition and culture.